Program Partisipasi Masyarakat Dalam Pencegahan Dan Pemberantasan Penyakit Tuberkolosis - Dwi Nopriyanto; Bahtiar, Bahtiar; Iwan Samsugito; Rita Puspa Sari; Syukma Rhamadani Faizal Nur; Naedy Ariady; Novita Sari; Dea Tri Regina; Riana Puryanti; Asmiranda Adelia P; Naomi Theresia Angkeli (Jurnal Pengabdian Kesehatan Masyarakat Mulawarman, 2024)
Tuberculosis is still a health problem in Indonesia and creates very complex problems not only in terms of health but also social, economic and cultural. Based on the low level of discovery and treatment, it is estimated that TB sufferers in East Kalimantan will double by 2024, where 75% of sufferers will be of productive age. The national strategy for controlling and preventing Tuberculosis in Indonesia 2020-2024 currently has a target of reducing cases to 65 per 100,000 population in 2030, including the East Kalimantan region. So, to make this happen, all parties need to play an active role through efforts to prevent and control tuberculosis. The right solution to this problem is to empower the community in efforts to prevent and control Tuberculosis. The aim of the community service activity program is carried out in the community in the Gunung Lingai Village area, Samarinda City, namely to increase knowledge, understanding and increase community awareness to prevent and eradicate Tuberculosis in the community and reduce the problems caused by people who have been identified as having the disease. Tuberculosis. The method used in this activity is a mediation method carried out by community groups, Tuberculosis program managers at the Youth Health Center and Tuberculosis cadres in Gunung Lingai Village together to increase community knowledge in preventing and eradicating and increasing the success of Tuberculosis therapy in the local area.